2009
DOI: 10.1074/jbc.m808050200
|View full text |Cite
|
Sign up to set email alerts
|

Endophilin B1/Bif-1 Stimulates BAX Activation Independently from Its Capacity to Produce Large Scale Membrane Morphological Rearrangements

Abstract: Endophilin B1/BAX-interacting factor 1 (Bif-1) is a protein that cooperates with dynamin-like protein 1 (DLP1/Drp1) to maintain normal mitochondrial outer membrane (MOM) dynamics in healthy cells and also contributes to BAX-driven MOM permeabilization (MOMP), the irreversible commitment point to cell death for the majority of apoptotic stimuli. However, despite its importance, exactly how Bif-1 fulfils its proapoptotic role is unknown. Here, we demonstrate that the stimulatory effect of Bif-1 on BAX-driven MOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 56 publications
(58 reference statements)
1
45
1
Order By: Relevance
“…Most interestingly, Bif-1 was recently found to modulate autophagy by interacting with beclin-1-VPS34 complex through the UVRAG protein (Takahashi et al, 2007). Moreover, a recent study suggested that Bif-1 might act as a driving force for autophagosome formation (Etxebarria et al, 2009) (reviewed by Takahashi et al, 2009). In this study, we discovered that Bif-1 is required for GSK-3 inhibitor-induced autophagic response, necrosis and apoptosis.…”
Section: Introductionmentioning
confidence: 55%
“…Most interestingly, Bif-1 was recently found to modulate autophagy by interacting with beclin-1-VPS34 complex through the UVRAG protein (Takahashi et al, 2007). Moreover, a recent study suggested that Bif-1 might act as a driving force for autophagosome formation (Etxebarria et al, 2009) (reviewed by Takahashi et al, 2009). In this study, we discovered that Bif-1 is required for GSK-3 inhibitor-induced autophagic response, necrosis and apoptosis.…”
Section: Introductionmentioning
confidence: 55%
“…99,[102][103][104] However, Kushnareva et al 95 found no evidence supporting a role for these proteins in Bax-induced permeabilization of isolated MOM vesicles. Chemical compounds (mDivi-1 analogs) that had been shown to inhibit Drp1's yeast ortholog, Dnm1, also inhibit MOMP in mammalian cells, 105 and some mDivi-1 analogs blocked BAX-induced pore formation in rat liver and Xenopus MOM vesicles.…”
Section: Bax Monomers Are a Driving Force For Membrane Perturbationmentioning
confidence: 99%
“…We gathered different lines of evidence supporting that active forms of Bax and Bak form toroidal pores of proteolipidic nature. On the one hand, we found that pore formation by Bax and Bak is linked to changes in the intrinsic monolayer curvature and line tension of the membrane, two physical properties known to be critical for toroidal pore formation (17,18,26,31,32). On the other hand, x-ray diffraction experiments demonstrated that a peptide derived from the central helix of Bax (Bax ␣5) forms pores in supported bilayers containing lipid molecules in their lumen (33), consistent with functional and structural information obtained with this peptide in a variety of model membrane systems (34 -36, 41-43).…”
mentioning
confidence: 92%